Relationship between the rs333 Polymorphism in the CC Chemokine Receptor Type Five (CCR5) Gene and Immunological Disorders: Data from a Meta-Analysis - Pereira da Silva, Felipe Rodolfo; Bentes Leal, Alessandro Luiz Araújo; Koga, Reyce Santos; Pereira Alves, Even Herlany; Pinho de Lira, John Arlley Sousa; Alves da Silva, Humbelina; Rodríguez Ayala, Karen Neisman; Carneiro Gomes, Paulo Roberto; Cunha Pereira, Anna Carolina Toledo da; Pereira Vasconcelos, Daniel Fernando (International Journal of Statistics in Medical Research, 2021)
Introduction: Inflammatory Bowel Disease (IBD), periodontitis and Systemic Lupus Erythematous (SLE) are multifactorial diseases, one of the factors in the course of these diseases is the rs333 polymorphism in the CC chemokine receptor type five (CCR5) gene. However, the results remain contradictory. Therefore, we aimed to perform a meta-analysis evaluating the relation between this polymorphism and the aforementioned conditions. Material and Methods: A search in the literature was performed in diverse scientific and medical databases for studies published before June 22, 2020. The data were extracted from the studies and the statistical evaluation was performed by the calculations of statistical heterogeneity (I²), Odds Ratio (OR) with 95% of Confidence Intervals (CI) and publication bias. The values of P<0.05 were considered as significant for all calculations. Results: 19 articles with 21 case/control studies in 4,304 case patients and 3,492 controls were included. The meta-analysis showed a non-significant association among the rs333 polymorphism and IBD (OR = 1.05, 95% CI: 0.91-1.20, P = 0.51), periodontitis (OR = 0.86, 95% CI: 0.64-1.17, P = 0.34) or SLE (OR = 1.00, 95% CI: 0.56-1.80, P = 1.00) under the allelic model or for any other performed calculation. There were no obvious publication bias in the analyses. Conclusion: In conclusion, this current meta-analysis evidenced the non-significant relation among the rs333 polymorphism and the risk of IBD, periodontitis or SLE. Further studies are required to validate our data.